Minimally invasive approach to the adrenal gland in obese patients with Cushing's syndrome. Issue 5 (3rd September 2019) - Ortenzi, Monica; Balla, Andrea; Ghiselli, Roberto; Vergari, Roberto; Silecchia, Gianfranco; Guerrieri, Emanuele; Maria Paganini, Alessandro; Guerrieri, Mario
Abstract: Introduction: The combination of Cushing's syndrome and obesity, one of the most common manifestations of the syndrome itself, may be associated with the worsening of post-operative outcomes in case of laparoscopic adrenalectomy. This study focused on the laparoscopic treatment of Cushing's syndrome with the purpose to identify any relevant difference between morbidly obese, mildly obese and non-obese patients. Material and methods: Patients were retrospectively divided into three groups according to their Body Mass Index (BMI). Demographic characteristics, operative and post-operative data were collected. Data about different hemostatic devices were also collected and compared. Differences were analyzed with the Fisher's exact test for categorical variables, and the Mann-Whitney test for continuous variables. Results: No differences were found in operative time (101.5 ± 50.9 min; p  = .919), conversion rate (2.6%; p  = .655) or length of stay (4.3 ± 2.9 days; p  = .886). Complication rate was 3% ( p  = .32), without any mortality. 95% of patients showed a complete resolution of hypercotisolyism-related symptoms, and a mean BMI reduction of 5 ± 3.2 kg/m 2 (follow up = 6.3 ± 4.2 years).Conclusions: Laparoscopic adrenalectomy is safe and feasible in obese patients affected with Cushing's disease and it can lead to the resolution of the related symptoms.